The clinical behavior of well differentiated liposarcoma can be extremely variable: A retrospective cohort study at a major sarcoma center. Issue 8 (3rd May 2018) - Keung, Emily Z.; Ikoma, Naruhiko; Benjamin, Robert; Wang, Wei‐Lien; Lazar, Alexander J.; Feig, Barry W.
Abstract : Background: The pathogenesis of well differentiated liposarcoma (WDLPS) is poorly understood and pathologic characterization is often challenging. Descriptive terms (such as sclerosing, myxoid, inflammatory, spindle cell) are frequently encountered in the pathology reports and are of unknown clinical significance. Methods: Sixty‐two patients with primary retroperitoneal WDLPS resected at our institution were identified (1996‐2011). Pathology reports of surgical resection specimens were retrospectively reviewed and descriptive qualifiers to the WDLPS diagnosis noted. Results: Descriptive qualifiers were associated with 36 (58%) cases. WDLPS with pathologic qualifiers were more likely to be larger (median size 32 vs 25.5 cm, P  = 0.01) and multifocal (36.1 vs 7.7%, P  = 0.01) at diagnosis, require concomitant organ resection at surgery (50 vs 23.1%, P  = 0.03), and have higher incidence of local recurrence (83.3 vs 38.5%, P  < 0.01). WDLPS with pathologic qualifiers showed significantly shorter local recurrence‐free survival (LRFS) and trend towards shorter distant recurrence‐free survival and overall survival. Use of pathologic qualifiers with a WDLPS diagnosis independently predicted risk of worse LRFS. Conclusions: Retroperitoneal WDLPS tumors characterized by pathologic descriptive qualifiers appear to behave more aggressively than their more typical counterparts. Further investigation is warranted to more consistently characterize and define the pathologic features commonly seen in WDLPS as these may impact patient outcomes.